Case study on the effect of media promotion on Zapin among university students in UiTM Malacca city campus / Muhammad Noor Taufik Abd Jalil - Abd Jalil, Muhammad Noor Taufik (2014)
Zapin is a great Malay folk dance. It brought to Malaysia by Arabic merchant and since then it's been assimilated with Malay culture especially in Johor Bahru. In these few years our government starts to take the initiative to protect this traditional culture from losing to today modernization. We have done a lot of things to make sure the continuation of this art. Although many things have been done but it still does not succeed in attracting audiences. That is why I like to find out what is going on, what really our youngster think, whether they still appreciate this kind of culture or they simply ignore them. The result that I got from my survey and observation is a positive feedbacks and that younger generation nowadays still love their own culture and they also want it to be able represented Malaysia. They also want to see a new style that can be used for zapin promotion maybe social media like facebook and twitter.